Optimizing occlusal schemes to reduce masticatory stress in resorbed class III jaw relations edentulous ridges: A systematic literature review - Sonia Nduma Nola Padang; Ismet Danial Nasution; Ricca Chairunnisa (Indonesia Prosthodontic Association, 2026)
Background: An unfavorable jaw relationship, such as Class III, contributes to uneven masticatory stress distribution, accelerating alveolar bone resorption and potentially resulting in a flattened ridge morphology. This condition directly impacts denture stability and retention. Therefore, selecting an appropriate occlusal scheme is essential to guide and balance masticatory forces, enabling more even and physiological stress distribution. However, there is currently no clear consensus on the most effective occlusal scheme for Class III jaw relationships with flat ridges. Objective:This systematic review aims to evaluate and synthesize current scientific evidence regarding the influence of different occlusal schemes on stress distribution in patients with Class III jaw relationships accompanied by flat alveolar ridges. Methods: Following the PRISMA guidelines. A comprehensive electronic search was conducted through PubMed, Cochrane, and ScienceDirect databases to identify relevant studies published between 2015 and 2025. The search strategy included keywords such as: (“alveolar ridge” AND “occlusal schemes”) AND (“stress distribution”), as well as (“alveolar ridge” OR “occlusal schemes”) AND (“stress distribution”). Results: Out of 1061 articles screened, five studies met the inclusion criteria. Lingualized and balanced occlusion demonstrated a more uniform stress distribution compared to monoplane occlusion, particularly in patients with Class III jaw relationships and flat ridges. Conclusions: Occlusal schemes play a crucial role in reducing masticatory stress, especially in patients with Class III jaw relationships and flattened alveolar ridges. Further research is recommended, particularly in vitro biomechanical studies using masticatory simulation models that better represent the clinical conditions of Class III patients with flat ridges. Keywords: occlusal schemes, stress distribution, alveolar ridges, Class III.